2012
DOI: 10.1186/1475-2875-11-439
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anopheles salivary antigens as individual exposure biomarkers to species-specific malaria vector bites

Abstract: BackgroundMalaria transmission occurs during the blood feeding of infected anopheline mosquitoes concomitant with a saliva injection into the vertebrate host. In sub-Saharan Africa, most malaria transmission is due to Anopheles funestus s.s and to Anopheles gambiae s.l. (mainly Anopheles gambiae s.s. and Anopheles arabiensis). Several studies have demonstrated that the immune response against salivary antigens could be used to evaluate individual exposure to mosquito bites. The aim of this study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…It is tempting to postulate that APCs could be overwhelmed with mosquito-derived peptides, leading to mosquito-specific responses that self-regulate antigen-presenting DCs even as these APCs simultaneously present smaller quantities of parasite-derived antigens. Mosquito-derived antigens are known to induce antibody responses (54)(55)(56)(57), and both saliva and sporozoites remain in the skin for up to 18 h postbite (58).…”
Section: Figmentioning
confidence: 99%
“…It is tempting to postulate that APCs could be overwhelmed with mosquito-derived peptides, leading to mosquito-specific responses that self-regulate antigen-presenting DCs even as these APCs simultaneously present smaller quantities of parasite-derived antigens. Mosquito-derived antigens are known to induce antibody responses (54)(55)(56)(57), and both saliva and sporozoites remain in the skin for up to 18 h postbite (58).…”
Section: Figmentioning
confidence: 99%
“…21,22 There have been a number of studies validating the detection of anti-mosquito salivary proteins as biomarkers for mosquito bite exposure. 21,[24][25][26][27][28][29][30] Although the different studies have all used different methods to assess immune response to mosquito salivary proteins, all suggest that antibodies to mosquito salivary proteins are effective biomarkers for exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, persons from Senegal and Marseille had low IgG responses to AgTRIO, which were not significantly different. In addition, a previous study with these groups of sera has shown that individuals from Senegal had IgG responses to selected A. gambiae components, while persons from Marseille did not (Ali et al, 2012), further suggesting that AgTRIO is not highly antigenic during a natural mosquito bite.…”
Section: Resultsmentioning
confidence: 89%
“…Many studies have characterized mosquito salivary gland proteins using different techniques, including genomics, transcriptomic approaches, and proteomic approaches (Ali et al, 2012; Almeras et al, 2010; Arca et al, 2005, 2007; Calvo et al, 2004, 2009, 2010; Kalume et al, 2005; Valenzuela et al, 2003). Using a yeast surface display library from RNA isolated from female A. gambiae mosquitoes, and probing it with A. gambiae SGE antiserum, allows for the selection of antigens independent of the limits of detection due to protein quantity in saliva.…”
Section: Discussionmentioning
confidence: 99%